If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(5x + 4) = 2(3m + -10) Reorder the terms: 2(4 + 5x) = 2(3m + -10) (4 * 2 + 5x * 2) = 2(3m + -10) (8 + 10x) = 2(3m + -10) Reorder the terms: 8 + 10x = 2(-10 + 3m) 8 + 10x = (-10 * 2 + 3m * 2) 8 + 10x = (-20 + 6m) Solving 8 + 10x = -20 + 6m Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-8' to each side of the equation. 8 + -8 + 10x = -20 + -8 + 6m Combine like terms: 8 + -8 = 0 0 + 10x = -20 + -8 + 6m 10x = -20 + -8 + 6m Combine like terms: -20 + -8 = -28 10x = -28 + 6m Divide each side by '10'. x = -2.8 + 0.6m Simplifying x = -2.8 + 0.6m
| 1/2q-1=6 | | 38-4x=5x+16 | | 7/8x+1/2=7/8 | | 34x+5=10 | | (6x+7/6)+(3/2)=-2x/7 | | -4-2x=12-8x | | x^4-18x^3+81x^2=0 | | 3(x+4)-4(x-3)= | | (6x+7/6)+(3/2)=-2 | | 2q-1=6 | | 4v^2-20v=0 | | 11-8x=139-36x | | 75-4x=14-8x | | x*3a=27 | | ((x-4)+1)/(x+1)=1/2 | | 5x^2+6x-12=2x | | 13b*17= | | 14n-21/7 | | 1/3x+5/6x=7/8 | | 8+(5-4x)-(1-x)=5x-2(x-3) | | 0.7/x=21 | | 7x+12=6+5x | | y=75+20x | | 8(c-2)-(c+3)= | | ((7x-1)/4)-1/3(2x-(1-x)/2)=19/3 | | 18(-x-2)-4(-9+3)=-14 | | 5m^2-9m+7m^2-2m= | | 17-x=12 | | 7a+7ab=2-3b | | 3.2n=n+7.8 | | 5x+(x+8)=-16-2x | | (7X-1)/4-(1/3)(2x-(1-x)/2)=19/3 |